Regional Head Policies In The Republic Of Indonesia During The Covid-19 Pandemic - Dwi Andayani Bs; Muhammad Rizqi Fadhlillah; Alif Sena Yudi Jastri (Fakultas Hukum Universitas Lampung, 2021)
The spreading of Covid-19 cases is happens so quickly to every countries around the world. In this case the local government are playing a huge role to control the spreading of the virus. The authority of regional heads in issuing various policies during the Covid-19 pandemic refers to Law Number 6 of 2018 concerning Quarantine, Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating Handling of Corona Virus Disease 2019 (Covid-19), Minister of Health Regulation Number 9 of 2020 concerning Guidelines for Large-Scale Social Restrictions in the Context of Accelerating Handling of Corona Virus Disease 2019 (COVID-19). The type of research method used in this research is normative research, namely research on library materials which are basic data in science is classified as secondary data, which relies on data collection tools in the form of library studies or document studies. The conclusion in this paper is the obstacles faced by regional heads in handling the Covid-19 pandemic, and its resolution includes the dominant authority of the central government in regulating and implementing PSBB. To address this problem, it is necessary to create good collaboration between the central government and local governments in regulating policies so that the handling of the COVID-19 pandemic is immediately resolved.